Role of intermediate metallic sub-layers in improving the efficiency of kesterite solar cells: concept and optimization, ISSN / e-ISSN 2053-1591 / 2053-1591 - Hichem, Ferhati; DJEFFAL Fayçal (Materials Research ExpressMaterials Research Express, 2018)
In this work, versatile CdS/Cu 2 ZnSnS 4 (CZTS) solar cell designs based on intermediate metallic sub-layers (Au, Ti, and Ag) engineering are proposed for enhancing light-scattering behavior and reducing recombination losses. The idea behind this work is to generate optical confinement regions in the CZTS absorber layer to achieve an improved absorption and appropriate antireflection effects. Moreover, the ultra-thin metal at the CZTS/Mo interface can be helpful for reducing the series resistance, where it behaves like a blocking layer for the Sulfur diffusion. We further combine the proposed designs with Particle Swarm Optimization (PSO)-based approach to achieve broadband absorption and boost the conversion efficiency. It is found that the optimized design with Ti sub-layer improves the CZTS solar cell properties, where it yields 31% improvement in short-circuit current and 60% in the power efficiency over the conventional one. Therefore, the optimized designs provide the opportunity for bridging the gap between improving the optical behavior and reducing the recombination losses.